History resurrected (Ideological metamorphoses of the global order) - Cvetković, Vladimir (Sociološki pregled, 2022)
The armed conflict in Ukraine has been at a rapid pace changing the economic, political, military, media and, consequently, ideological structure of the world order. The common divisions between liberalism, socialism, Fascism, conservativism, nationalism and other national derivatives of the Moderna, have started fading vis-a-vis the new, strictly moralistic, and necessarily Manichaean structure: ‘traditional’ vs. ‘non-traditional’ values. In this context, the attitude towards one’s own historical heritage shapes antagonistic ‘cultures of remembrance’, that divinise, and if need be, falsify the assumed civilisation roots. On this basis, new legitimation patterns for ethical, political and economic confrontation are (de) constructed, which also applies to the armies of major powers crossing swords. Others can only with a smaller or bigger amount of enthusiasm – and with the inevitable domestic perturbation – keep up with the global trends of post-modern revitalisation of the pre-modern legacy.
Keywords: international order; international politics; civilisation values; war